2012
DOI: 10.5923/j.env.20110101.02
|View full text |Cite
|
Sign up to set email alerts
|

Pollution in Water of Kasardi River Flowing along Taloja Industrial Area of Mumbai, India

Abstract: The area of study selected in the present investigation was Kasardi River which receives heavy discharge of waste effluent from the nearby Taloja industrial belt which is one of the fastest developing industrial belt of Mumbai. The study was performed to investigate the concentration of toxic heavy metals like chromium (Cr), cadmium (Cd), nickel (Ni), zinc (Zn), copper (Cu), lead (Pb) and iron (Fe) in river. It was observed that concentration of most of these heavy metals were much higher than the maximum perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 21 publications
4
67
0
1
Order By: Relevance
“…Since most of the Indian industries are situated along the banks of river and creek for easy availability of water and also disposal of the wastes. It is found that one-third of the total water pollution in India comes in the form of industrial effluent discharge, solid wastes and other hazardous wastes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Previous data on water pollution along creeks [18][19][20][21][22][23][24][25] points out to the need of systematic and regular monitoring of pollution level for further improvement in the industrial waste water treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Since most of the Indian industries are situated along the banks of river and creek for easy availability of water and also disposal of the wastes. It is found that one-third of the total water pollution in India comes in the form of industrial effluent discharge, solid wastes and other hazardous wastes [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Previous data on water pollution along creeks [18][19][20][21][22][23][24][25] points out to the need of systematic and regular monitoring of pollution level for further improvement in the industrial waste water treatment methods.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, at the end of each time period the pollution problem takes menacing concern. As a result in India there are sufficient evidences available related with the mismanagement of industrial wastes [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…This can allow conclusions to be drawn regarding sources of contamination. Since sediments act as a sinks and sources of contaminants in aquatic systems, chemical analysis for characterization of sediments also provides environmentally significant information about natural and anthropogenic influence on the water bodies [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The development of a business man as well as growing to a transformative processes environment adversely affect the quality of the natural environment, including on the aquatic environment [1][2][3][4][5][16][17][18][19][20][21][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][62][63][64][65][66][67][68][69][70].…”
Section: Introductionmentioning
confidence: 99%